Mining and floods: a systematic review of empirical studies on community resilience strategies and interventions - Mariam Bouzid; William J. Guerrero; Luz Elba Torres-Guevara; Dairo Steven Muñoz Pinzón; Carlos Daniel Montes Rodriguez; Lady Giovanna Rojas Pineda; Juan José Díaz Castro; Erika Cardona Patiño; Karol Elkjaer Mondragon Sanchez (The Extractive Industries and Society, 2026)

Evaluating the role of physical mechanisms as possible triggers for turbidity currents in a deep ocean seamount - Susana M. Lebreiro; Álvaro Peliz; Laura Antón; Sílvia Nave; M. Isabel Reguera; Rocío Lozano-Luz; Claire Waelbroeck; Simon Crowhurst; Belen Martrat; Jordi F. Lopez; Raphaël Hebert; Alejandra Lopez-Rodriguez (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Exploring the influence of wood ash, maize cob ash, and tequesquite (alkaline rock) on nixtamalization of maize - Gricelda Vázquez-Carrillo; Leticia García-Cruz; Aide Molina-Macedo; María de la Luz Marrufo-Diaz; Mario E. Rodriguez-Garcia; Rafael Mier-Sainz Trapaga; Charles Bett; Natalia Palacios-Rojas (International Journal of Gastronomy and Food Science, 2024)

Morphological changes in the fetal kidney induced by exposure to fluoride during pregnancy - Esaú Montañez-Rodriguez; Sabino Hazael Avila-Rojas; Ariana Guadalupe Jimenez-Dorantes; Juan Carlos León-Contreras; Rogelio Hernandez-Pando; José Manuel Arreola-Guerra; Casimiro Gerarduzzi; María Estela Meléndez-Camargo; Luz M. Del Razo; Olivier Christophe Barbier (Environmental Toxicology and Pharmacology, 2024)

Geological context and human exposures to element mixtures in mining and agricultural settings in Colombia - Oscar Florez-Vargas; Eugenio Vilanova; Carolina Alcaide; José A. Henao; Carlos A. Villarreal-Jaimes; Olga M. Medina-Pérez; Laura A. Rodriguez-Villamizar; Alvaro J. Idrovo; Luz H. Sánchez-Rodríguez (Science of The Total Environment, 2023)

Fruit juice and childhood obesity: a review of epidemiologic studies - Junichi R. Sakaki; Nancy R. Rodriguez; Maria-Luz Fernandez; Michael J. Puglisi; Ming-Hui Chen; Ock K. Chun (Critical Reviews in Food Science and Nutrition, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Recognizing Indigenous peoples’ and local communities’ rights and agency in the post-2020 Biodiversity Agenda - Victoria Reyes-García; Álvaro Fernández-Llamazares; Yildiz Aumeeruddy-Thomas; Petra Benyei; Rainer W. Bussmann; Sara K. Diamond; David García-del-Amo; Sara Guadilla-Sáez; Natalia Hanazaki; Nicolas Kosoy; Margarita Lavides; Ana C. Luz; et al. (Ambio, 2022)
The Convention on Biological Diversity is defining the goals that will frame future global biodiversity policy in a context of rapid biodiversity decline and under pressure to make transformative change. Drawing on the work of Indigenous and non-Indigenous scholars, we argue that transformative change requires the foregrounding of Indigenous peoples’ and local communities’ rights and agency in biodiversity policy. We support this argument with four key points. First, Indigenous peoples and local communities hold knowledge essential for setting realistic and effective biodiversity targets that simultaneously improve local livelihoods. Second, Indigenous peoples’ conceptualizations of nature sustain and manifest CBD’s 2050 vision of “Living in harmony with nature.” Third, Indigenous peoples’ and local communities’ participation in biodiversity policy contributes to the recognition of human and Indigenous peoples’ rights. And fourth, engagement in biodiversity policy is essential for Indigenous peoples and local communities to be able to exercise their recognized rights to territories and resources.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

In vitro mycorrhization of the rubber tree Hevea brasiliensis Müll Arg - Tiffany Sosa-Rodriguez; Hervé Dupré de Boulois; Françoise Granet; Sylvie Gaurel; Luz-Marina Melgarejo; Marc-Philippe Carron; Stéphane Declerck (In Vitro Cellular & Developmental Biology - Plant, 2013)

The droughts of 1997 and 2005 in Amazonia: floodplain hydrology and its potential ecological and human impacts - Javier Tomasella; Patrícia F. Pinho; Laura S. Borma; José A. Marengo; Carlos A. Nobre; Olga R. F. O. Bittencourt; Maria C. R. Prado; Daniel A. Rodriguez; Luz A. Cuartas (Climatic Change, 2013)

Association of matrix metalloproteinase-2 gene promoter polymorphism with myocardial infarction susceptibility in a Mexican population - Ivan Delgado-Enciso; Nelida A. Gonzalez-Hernandez; Luz M. Baltazar-Rodriguez; Rebeca O. Millan-Guerrero; Oscar Newton-Sanchez; Alfonso Bayardo-Noriega; Alfonso Aleman-Mireles; Irma G. Enriquez-Maldonado; Ma J. Anaya-Carrillo; Augusto Rojas-Martinez; Rocio Ortiz-Lopez (Journal of Genetics, 2009)

A potential function of endocannabinoids in the selection of a navigation strategy by rats - Pavel E. Rueda-Orozco; Edgar Soria-Gomez; Corinne J. Montes-Rodriguez; Marina Martínez-Vargas; Oscar Galicia; Luz Navarro; Oscar Prospero-García (Psychopharmacology, 2008)

Polymorphism in the Matrix Metalloproteinase-2 Gene Promoter is Associated with Cervical Neoplasm Risk in Mexican Women - Luz M. Baltazar-Rodriguez; Aristoteles Anaya-Ventura; Maricela Andrade-Soto; Elisa A. Monrroy-Guizar; Jose R. Bautista-Lam; Gregorio Jonguitud-Olguin; Friedman R. Cepeda-Lopez; Veronica A. Centeno-Aguilar; Nelida A. Gonzalez-Hernandez; Alejandro D. Soriano-Hernández; Mario Ramirez-Flores; Angel Lugo-Trampe; et al. (Biochemical Genetics, 2008)